Eragrostis (Poaceae: Chloridoideae: Eragrostideae: Eragrostidinae) of Peru. - Peterson, P.M. (2007)
A taxonomic treatment of Eragrostis Wolf for Peru is given. Twenty-three species and three subspecies of Eragrostis are recognized in the study area. Fifteen species of Eragrostis are native to Peru, and eight are adventive or introduced. Eragrostis attenuata Hitchc., E. pilgeri Fedde, and E. magna Hitchc. are endemic to Peru. Eragrostis lurida subsp. contracta (Pilg.) P. M. Peterson & Sa´nchez Vega, native to Ecuador and Peru, and E. pilgeri subsp. ancashensis (P. M. Peterson, Refulio & Tovar) P. M. Peterson & Sa´nchez Vega, native to Peru, are new combinations. Keys for determining the species, descriptions, distributions, specimens studied, illustrations, synonymies, and a brief discussion of caryopsis morphology for all native and adventive species of Eragrostis in Peru are provided. The names E. andicola R. E. Fr., E. contracta Pilg., E. tristis Jedwabn., and Poa mexicana Hornem. are lectotypified.